Women in top management: Performance of firms and open innovation - Safdar Husain Tahir; Muhammad Rizwan Ullah; Gulzar Ahmad; Nausheen Syed; Alia Qadir (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
The lack of women's presence in firms' top management positions reflects gender equity problems, especially in South Asia, including Pakistan, and contours a firm's financial behavior. Based on the underpinning of the conceptual framework developed by a combination of fourteen femininity theories, the current study investigates women's induction in top management and its impact on a firm's financial behavior. We collected data from annual reports of 60 non-financial firms listed at the Pakistan Stock Exchange (PSX) for 2013-2019. The study uses the return of assets (ROA), firm's stability (FSTB), and risk-taking behavior (RTB) as dependent variables. Meanwhile, board gender diversity (BGD), female CEO (FCEO), female director-general (FDG), and female in audit committee (FIAC) are taken as independent variables. A multiple regression diagnostics approach is applied to analyze the data. The study reveals the positive impact of BGD on ROA and FSTB. However, this effect is adverse to RTB. The FIAC shows a positive (negative) impact on ROA (RTB). It also finds a negative impact of FCEO and FDG on ROA and FSTB.
Keywords: 650; women; feminism; feminist theories; performance; risk; stability; top management